Carbetocin at Elective Cesarean Delivery: A Sequential Allocation Trial to Determine the Minimum Effective Dose. Issue 3 (September 2015) - Khan, M.; Balki, M.; Ahmed, I.; Farine, D.; Seaward, G.; Carvalho, J.C.A.
Abstract : ( Can J Anesth. 2014;61:242–248)